Campaign Leave Time for Incumbents: Differences between General Election and Regional Head Election Regimes: Waktu Cuti Kampanye Bagi Incumbent: Perbedaan Rezim Pemilihan Umum dan Pemilihan Kepala Daerah - Riqiey, Baharuddin; Mubarok, Ahmad Zaky; Farisi, Gusti Muhammad Reyhan; Hadi, Syofyan (Jurnal Konstitusi, 2025)
Constitutional Court Decision Number 85/PUU-XX/2022 explicitly unified the Regional Head Election (Pilkada) regime with the General Election (Pemilu) regime. However, inconsistencies persist, particularly regarding campaign leave for incumbents. Unlike the General Election regime, the Pilkada regime mandates full leave during the campaign period. This discrepancy creates legal uncertainty, intolerable injustice, and discrimination. This study aims to analyse the applicability of Article 70(3) of Law No. 10/2016 in light of the aforementioned Constitutional Court Decision, highlighting the urgency of regulatory harmonisation. This research employs a doctrinal legal research method, drawing on statutory, conceptual, and case approaches. The results show that the differing regulations regarding incumbent campaign leave have indeed caused legal uncertainty, intolerable injustice, and discrimination among candidates. Therefore, this study concludes that legislators must harmonise these regulations and codify them into an omnibus electoral law to ensure consistency.